The evolutionary conserved FOXJ1 target gene Fam183b is essential for motile cilia in Xenopus but dispensable for ciliary function in mice - Anja Beckers (Nature Portfolio, 2018)
Abstract The transcription factor FOXJ1 is essential for the formation of motile cilia throughout the animal kingdom. Target genes therefore likely constitute an important part of the motile cilia program. Here, we report on the analysis of one of these targets, Fam183b, in Xenopus and mice. Fam183b encodes a protein with unknown function which is conserved from the green algae Chlamydomonas to humans. Fam183b is expressed in tissues harbouring motile cilia in both mouse and frog embryos. FAM183b protein localises to basal bodies of cilia in mIMCD3 cells and of multiciliated cells of the frog larval epidermis. In addition, FAM183b interacts with NUP93, which also localises to basal bodies. During frog embryogenesis, Fam183b was dispensable for laterality specification and brain development, but required for ciliogenesis and motility of epidermal multiciliated cells and nephrostomes, i.e. the embryonic kidney. Surprisingly, mice homozygous for a null allele did not display any defects indicative of disrupted motile ciliary function. The lack of a cilia phenotype in mouse and the limited requirements in frog contrast with high sequence conservation and the correlation of gene expression with the presence of motile cilia. This finding may be explained through compensatory mechanisms at sites where no defects were observed in our FAM183b-loss-of-function studies.